trans-Diaquabis[5-carboxy-2-(3-pyridyl)-1H-imidazole-4-carboxylato-κ2N3,O4]manganese(II) - Li-Zhuang Chen (Acta Crystallographica Section E, 2008)
In the title compound, [Mn(C10H6N3O4)2(H2O)2], synthesized by hydrothermal reaction, the MnII ion lies on an inversion centre and displays a distorted octahedral coordination geometry defined by the two imidazole N atoms and two carboxylate O atoms of the two trans-standing chelate ligands, and two O atoms of the water molecules. A two-dimensional supramolecular architecture is formed via N—H...O, O—H...N and O—H...O hydrogen-bonding interactions.